The Alienated City in 21st Century Cinema: A Socio-Critical Analysis - García López, Javier (Street Art & Urban Creativity, 2024)
This paper delves into the cinematic representation of the decaying city in contemporary cinema. The main objective is to understand how contemporary cinema reflects and comments on the complex dynamics of urban life in the 21st century, as well as its potential to inspire social and political changes towards a fairer, more sustainable, and habitable city. Through a socio-critical approach, employing the method of discursive analysis, a selection of films exploring urban realities marked by decay, social marginalization, alienation, and environmental crisis is examined. This representation is framed within the current socio-historical context, characterized by globalization, economic inequality, and massive urbanization. The analysis focuses on how these films offer a sharp critique of urban dynamics and the social, political, and environmental problems affecting contemporary cities. Themes such as gentrification, racial and economic segregation, urban environmental degradation, infrastructure collapse, and interpersonal disconnection in hyper-connected urban environments are explored. Additionally, the role of cinema as a tool for awareness and social activism is examined, highlighting how these cinematic representations not only serve as a mirror of urban reality but also as calls to action and critical reflection on the transformation and future of our cities.